PENGARUH MODEL PEMBELAJARAN BLENDED LEARNING PADA TEMATIK TEMA CUACA DENGAN MENGGUNAKAN MEDIA PEMBELAJARAN APLIKASI CANVA TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA SISWA KELAS 3 SD - Dwi Puspita Sari (PGSD UMN Al-Washliyah, 2022)
This study aims to determine the influence of blended learning models on thematics using the canva application on students' problem-solving ability. The population in this study was all grade III students totaling 75 students. Meanwhile, the sample was 30 students. This research is a quantitative research with a type of Quasi-Experimental research with a Nonequivalent Control Group Design design. The instrument used in this study was a test. From the results of the study obtained the average prettest value for the experimental class was 55.50 and the pretest for the control class was 39.17. Then the two classes were given different treatment, so that the average score of the posttest of the experimental class was 77.67 and the control class was 74.33. Hypothesis testing is carried out by t-test. From the calculation results obtained tcount = 6.34 > ttable = 2.05 with dk = 28 and the real level α = 0.05. It can be seen that tcount > ttable, so Ho is rejected and Ha is accepted. So the conclusion of this study is that the blended learning model with the canva application affects students' problem-solving ability in thematic learning of weather themes in grade III SD Negeri 105292 Bandar Klippa.